Subjective well-being among Latino day laborers: Examining the role of religiosity, social networks, and cigarette use - Javier F. Boyas; Pamela Valera; Erika Ruiz (Tabriz University of Medical Sciences, 2018)
Background: Latino day laborers (LDLs) experience chronic stressors, that adversely affects their subjective well-being (SWB). The purpose of the study was to determine whether LDLs' demographics characteristics, religiosity, social networks, and cigarette use were significantly associated with SWB. Methods: Approximately 150 LDLs from 4 informal day laborer sites in Dallas and Arlington,Texas, participated in the cross-sectional survey. Informed consent was obtained from all participants and data on SWB were collected face-to-face from April 2013 through July 2013.Results: Most respondents were of Mexican ancestry, (n = 112; 75%), were foreign-born (n =140; 93%), and undocumented (n = 108; 72%). LDLs reported a mean satisfaction with life scoreof 19.07 (SD=8.52). Thirty percent of LDLs reported not smoking any cigarettes in the past 30 days. However, 20% reported smoking 20-39 cigarettes, while another 20% reported smoking or more cigarettes in the past 30 days. Hierarchical multiple regression results indicated that marital status (β = 0.13, P ≤ 0.05), disconnectedness to friends (β = 0.21, P ≤ 0.001), the influence of religion on life (β = 0.57, P ≤ 0.01), frequency of attendance to religious institution (β = 0.11,P ≤ 0.005), and cigarette use (β = -0.15, P ≤ 0.05) were significantly associated with the SWB appraisals of LDLs. Conclusion: These findings show that LDLs are resilient and rely on non economic factors to enhance their perceived quality of life. The results underscore the need to identify pathways to improve SWB among LDLs. Doing so may address the broader mental health and occupational health disparities gaps that affect LDLs.